Abnormal expression of RNA polymerase II‐associated proteins in muscle of patients with myofibrillar myopathies. Issue 6 (25th May 2015) - Guglielmi, Valeria; Marini, Matteo; Masson, Émilie Fiola; Malatesta, Manuela; Forget, Diane; Tomelleri, Giuliano; Coulombe, Benoit; Vattemi, Gaetano
Abstract : Aims: Myofibrillar myopathies (MFMs) are a group of inherited or sporadic neuromuscular disorders characterized morphologically by foci of myofibril dissolution, disintegration of the Z‐disk and insoluble protein aggregates within the muscle fibres. The sequential events leading to muscle fibre damage remains largely unknown. Methods and results: We investigated the expression and the cellular localization of RNA polymerase II (RNAPII)‐associated proteins (RPAPs) in muscle biopsies from patients with genetically proven and sporadic MFMs. Our data demonstrated that RPAP2, and to a lesser extent GPN1/RPAP4, are accumulated focally in the cytoplasm of MFM muscle fibres in which they co‐localize with POLR2A/RPB1, the largest subunit of RNAPII, and correspond to αB‐cystallin deposits in distribution and staining intensity. No abnormal staining for RPAP2 has been observed in muscle of patients with central cores, minicores and neurogenic target fibres. Conclusions: Together, these findings could provide new insights into the molecular pathogenesis of MFMs and suggest that RPAP2 immunostaining can be a useful diagnostic tool to depict protein aggregates in MFMs.